Controlling concatenation in germanium(I) chemistry through hemilability - Caise, A; Griffin, LP; Heilmann, A; McManus, C; Campos, J; Aldridge, S (Wiley, 2021)
We present a novel approach for constructing chains of Group 14 metal atoms linked by unsupported metal–metal bonds that exploits hemilabile ligands to generate unsaturated metal sites. The formation/nature of catenated species (oligo-dimetallynes) can be controlled by the use of (acidic/basic) “protecting groups” and through variation of the ligand scaffold. Reduction of ArNiPr2GeCl (ArNiPr2=2,6-(iPr2NCH2)2C6H3)—featuring hemilabile NiPr2 donors—yields (ArNiPr2Ge)4 (2), which contains a tetrameric Ge4 chain. 2 represents a novel type of a linear homo-catenated GeI compound featuring unsupported E−E bonds. Trapping experiments reveal that a key structural component is the central two-way Ge=Ge donor-acceptor bond: reactions with IMe4 and W(CO)5(NMe3) give the base- or acid-stabilized digermynes (ArNiPr2Ge(IMe4))2 (4) and (ArNiPr2Ge{W(CO)5})2 (5), respectively. The use of smaller N-donors leads to stronger Ge-N interactions and quenching of catenation behaviour: reduction of ArNEt2GeCl gives the digermyne (ArNEt2Ge)2, while the unsymmetrical system ArNEt2GeGeArNiPr2 dimerizes to give tetranuclear (ArNEt2GeGeArNiPr2)2 through aggregation at the NiPr2-ligated GeI centres.